Penerapan Metode Takakura Sebagai Upaya Pengolahan Sampah Organik Skala Rumah Tangga Secara Mandiri Pada Generasi Muda - Yuvita Dian S; Musarofa Musarofa; Dio Aji Saputra; Debita Dwi Putri (Indonesian Journal Publisher, 2023)
Takakura method is one of making compost method on a small scale and with continuous production. This method has advantages compared to other method, beside its practis, this ,ethode does not require any special skills to make it. This is consider suitable to be applied in order to teach waste management in the youth environment, especially to increase the knowledge and awareness of adolescents as human beings “the waste producer”. Gresik is one of the supporting areas for development of Surabaya, which is characterized by the development of settlement clusters. The growth and development of settlements in areas bordering the city of Surabaya is an indicator o the increasingly widespread socio-economic activities of the urban community towards the Surabaya-gresik border. The pattern of waste waste management that dominates in this area is an individual pattern where waste is usually burned in the fron/back yard of each residents or it is disposed of into rivers. This activities is carried out especially teenagers in Karang Taruna, Pengalangan Village, Gresik ragenciy can become agents of change in society and can be more responsible for the waste they produced. In addition, this training activitiey can also be a provision for teenagers to be more empowered and foster an entrepreneurial spirit both individually or groups